Tailoring interventions to suit self-reported format preference does not decrease vaccine hesitancy - Mäki Karl Otto; Karlsson Linda C.; Kaakinen Johanna K.; Schmid Philipp; Lewandowsky Stephan; Antfolk Jan; Soveri Anna (Public Library of Science, 2025)
Individually tailored vaccine hesitancy interventions are considered auspicious for decreasing vaccine hesitancy. In two studies, we measured self-reported format preference for statistical vs. anecdotal information in vaccine hesitant individuals, and experimentally manipulated the format in which COVID-19 and influenza vaccine hesitancy interventions were presented (statistical vs. anecdotal). Regardless of whether people received interventions that were in line with their format preference, the interventions did not influence their vaccine attitudes or vaccination intentions. Instead, a stronger preference for anecdotal information was associated with perceiving the material in both the statistical and the anecdotal interventions as more frustrating, less relevant, and less helpful. However, even if the participants reacted negatively to both intervention formats, the reactions to the statistical interventions were consistently less negative. These results suggest that tailoring COVID-19 and influenza vaccine hesitancy interventions to suit people’s format preference, might not be a viable tool for decreasing vaccine hesitancy. The results further imply that using statistics-only interventions with people who hold anti-vaccination attitudes may be a less risky choice than using only anecdotal testimonies.